calculați a) (3-√2)(3+√2)= b) (1-√3)(2-√3)= c) (√3+√2)(√3-√2) d) (√8+√2)(√27-√3)
e) (√8+√72):(√18+√50-√32=
Răspunsuri la întrebare
Răspuns de
0
Răspuns:
Explicație pas cu pas:
a) a²-b²⇒3²-(√2)²=9-2=7
b) 2-√3-2√3+3=5-3√3
c) a²-b² ⇒√3²-√2²=3-2=1
d) (2√2+√2)(3√3-√3)=3√2×2√√3=6√6
e) (2√2+√8·√9):(√2·√9+√25·√2-√16·√2)=(2√2+3·2√2):(3√2+5√2-4√2)=
=8√2:4√2=2
Alte întrebări interesante
Matematică,
8 ani în urmă
Engleza,
8 ani în urmă
Limba română,
8 ani în urmă
Matematică,
8 ani în urmă
Matematică,
9 ani în urmă
Limba română,
9 ani în urmă
Limba română,
9 ani în urmă